STUDY OF THE CROSS SHORE PROFILE STABILITY ON THE ARTIFICIAL BEACH NOURISHMENT (Phisical Model Using Small Scale 2-D Model) - Yuwono, Nur; Triatmaja, Radianta; Nizam, Nizam; Setyandito, Oki (2009)
ndonesia’s long coastal line may provide significant resource if managed properly. The coastal area serves as tourists’ destination, hub for inter modes between land and water transports, and many other businesses as well as natural resources. Beach conservation is therefore important and should be carried out whenever necessary and feasible. Artificial beach nourishment is one of the alternatives for coastal conservation method, especially to protect the beach from the effect of climate changes. Artificial beach nourishment provide more space in coastal area and produce more natural appearance when compare with hard structure coastal protection (breakwater). The beach profile characteristics especially the stability of sand slope under various wave conditions is probably the most important issue relevant to artificial beach design. Hence, a thorough study concerning artificial beach stability is carried out and reported in this paper. The cross-shore profile stability was studied using experimental approaches. Two- dimensional physical model was set up in the laboratory flume. The flume was equipped with regular wave generator. At one end of the flume, an artificial beach model was constructed. The range of sand grain size (d50) was < 0.25 mm. The initial slopes (n) of the artificial beach are n =1:6. Initially, the beach slopes are straight. The wave periods are varied from 1 to 4 seconds at model scale. The water depth is 20 cm. The results indicate that the beach slopes are adjusted due to wave attack to form either steeper or flatter stable slopes. The stable beach slope (nf) is a function of wave height (H), wave period (T), grain size diameter of sand particle (d50), and slope (n). The non dimensional graph between parameters shows that the higher is the wave height (H), the steeper is the stable slope (nf). The range of stable slopes (nf) are 4 ≤n ≤ 14. The smaller is the wave period (T), the steeper is the stable slope (nf) and depend on the wave height (H). It was observed that the sand particles at the lower part of the slope is transported upward and deposited at a higher part of the slope and vice versa.